Does Volunteering in a Language Learning Centre Help Non-Native English Speaking Students' Emotional Well-Being? - Hilda Freimuth; Joe Dobson (Cranmore Publishing, 2021)
Feeling connected as one navigates life as a post-secondary student is a challenge for many students, both domestic and international. Many non-native speakers of English may not feel a sense of belonging or social connectedness at university and have emotional and other needs hindering their adjustment and success at university. Institutions often have various opportunities for students to volunteer at events, support centres, and other university units. Self-access centres, such as language learning centres and writing centres, have become common at many institutions and often have many student volunteers, making these an ideal environment for research on students. This study took place in one of these centres at a university in Canada - a language learning centre. In this study, researchers used a mixed methods approach to explore student volunteer perceptions. Survey responses that related to the emotional well-being of student volunteers were highlighted for this study. The data from the survey were then cross-referenced with the transcripts of the focus group study for further confirmation. Findings indicate that the act of volunteering in the centre made an impact on student volunteers' emotional well-being. It gave students a sense of belonging and the feeling that they were part of a greater community. It also helped reduce loneliness and build self-esteem.